The Preference of Choosing Topic for Arranging Final Project Title in Early Childhood Education at State University of Semarang Year Academic 2010-2015 - Malika, Laila; Waluyo, Edi (BELIA: Early Childhood Education Papers, 2017)
The study was based on the variety of final project title which had been arranged by the students of the Early Childhood Education (PG PAUD) in State University of Semarang (UNNES). It caused the confusion of the students which would make a final project. The purposes of the study were (1) To know about the preference of choosing topic for arranging final project by the students of PG PAUD UNNES Year Academic 2010-2015, (2) To know the factors which raised the preference of choosing topic for arranging final project by the students of PG PAUD UNNES Year Academic 2010-2015, (3) To know what topic had not been chosen by the students of PG PAUD UNNES for arranging final project Year Academic 2010-2015.The study used descriptive method which utilized quantitative approach. The data collecting was gathered by using interview and documentation. It took PG PAUD UNNES as the research location. The informant was consisted of one Head of the Program and three supervisors of the final project. The data analysis used analysis descriptive statistics, crosstab, and Chi Square analysis by using SPSS version 19. The result gathered from 240 final projects of PG PAUD UNNES Year Academic 2010-2015 showed that: 50 topics were about the Early Childhood growth and development; 32 topics were about educator and the educational staff; and 158 topics were about learning process of Early Childhood. (1) The students chose the topics about the learning process of Early Childhood, (2) The preferences background were because the students looked only the previous final projects and lacked of reading habit, (3) The material or subject of final project topic rarely chose was believed as the uninterested topic and difficult references.It needed sustainable experiments for five years in order to avoid the surge of the preferences in choosing topic. The surge could bring out the saturated variables in Early Childhood experiments.